Gen Alpha Slang in 'Last Rizzday Night' Lyrics: A Semantic Analysis - Subhan, Muhammad; Firdaus, Dadan; Yatmikasari, Ika (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the semantic evolution of Generation Alpha's slang as reflected in the lyrics of Jelly House's YouTube song Last Rizzday Night. As a digital-native generation, Gen Alpha frequently reshapes language through their engagement with digital media. Analysing 15 slang terms, including